2022
DOI: 10.3390/cancers14040926
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disorders, Risk Factors and Sleep Treatment Needs of Adolescents and Young Adult Childhood Cancer Patients in Follow-Up after Treatment

Abstract: Background: Sleep disorders negatively impact adolescent and young adult childhood cancer patients’ physical and psychosocial health. Early recognition improves timely treatment. We therefore studied the prevalence of subjective sleep disorders, risk factors and sleep treatment needs after completion of childhood cancer treatment. Methods: Childhood cancer patients (12–26 years old), ≥6 months after treatment, were invited to fill out the Holland Sleep Disorders Questionnaire, which distinguishes six sleep dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that patients have a need for support for their sleep and fatigue symptoms after active treatment has ended [ 4 , 56 , 57 ]. However, they often experience barriers with reporting sleep problems to their healthcare professional [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that patients have a need for support for their sleep and fatigue symptoms after active treatment has ended [ 4 , 56 , 57 ]. However, they often experience barriers with reporting sleep problems to their healthcare professional [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data for the current study were collected during part 1 of the study, with a cross-sectional national cohort design. For more information on the procedures and characteristics of responders and non-responders to the questionnaires, please see Peersmann et al [ 4 ]. Adolescents and young adults in the Netherlands that were included in the Dutch Childhood Oncology Group registry (DCOG; patients that were 6 months up to 5 years after diagnosis) or the Dutch Childhood Cancer Survivorship Study (DCC-SS LATER registry; patients that were 5–10 years after diagnosis) were eligible if they: (1) were aged ≥12 years old at the time of study; (2) were diagnosed with cancer or a non-malignant/low-grade tumor for which oncologic follow-up was required, before the age of 19 years; (3) were diagnosed within the last 10 years; and (4) had finished their last cancer treatment at least 6 months prior.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep problems are common during and after treatment for childhood cancer [ 1 , 2 , 3 , 4 ] and they are related to a lower quality of life [ 5 , 6 , 7 ]. The prevalence of sleep problems in children with cancer during treatment ranges from 74 to 95% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%